Heat shock‐induced arrests in different cell cycle phases of rat C6‐glioma cells are attenuated in heat shock‐primed thermotolerant cells - Kühl, N. M. (Cell Prolif, 2002)
The response kinetics of rat C6 glioma cells to heat shock was investigated by means of flow cytometric DNA measurements and western blot analysis of HSP levels. The results showed that the effects on cell cycle progression are dependent on the cell cycle phase at which heat shock is applied, leading to either G1 or G2/M arrest in randomly proliferating cells. When synchronous cultures were stressed during G0 they were arrested with G1 DNA content and showed prolongation of S and G2 phases after release from the block. In proliferating cells, HSC70 and HSP68 were induced during the recovery and reached maximum levels just before cells were released from the cell cycle blocks. Hyperthermic pretreatment induced thermotolerance both in asynchronous and synchronous cultures as evidenced by the reduced arrest of cell cycle progression after the second heat shock. Thermotolerance development was independent of the cell cycle phase. Pre‐treated cells already had high HSP levels and did not further increase the amount of HSP after the second treatment. However, as in unprimed cells, HSP reduction coincided with the release from the cell cycle blocks. These results imply that the cell cycle machinery can be rendered thermotolerant by heat shock pretreatment and supports the assumption that HSP70 family members might be involved in thermotolerance development.